A SHORT STORY READING SECTION AS AN ALTERNATIVE WAY TO IMPROVE STUDENT’S LITERACY IN SD N 6 PANJER KEBUMEN - Dwi Novitasari; Eka Fajriatul Janah; Muhamad Chamdani (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
The goverment made changes to the Indonesian education curriculum of the education unit level curriculum into the curriculum of 2013. Changes in the curriculum in 2013 lies in the preparation of the RPP (Lesson Plan) and the ability of literacy. The emphasis on the preparation of the RPP has been resolved with the holding of training, but to literacy still unwell. One way to improve the literacy skills is through the reading of short stories. The reading of the short story aims to help improve reading skills and knowledge of sentence patterns, so it can be an idea to create an article. The focus on this study include: (1) The concept of reading a short story; (2) The impact of short story readings. These studies include: (1) The reading of short stories is an activity habituation to read a fictional narrative prose text .; (2) The impact resulting from the reading of short stories such as enhancing the knowledge, encourage the growth likes to read, and to foster the ability to write.